How small KIBS companies manage their intellectual capital? Towards an emergent km approach - Ettore Bolisani; Enrico Scarso; Malgorzata Zieba (Gdańsk University of Technology, Faculty of Management and Economics, 2014)
The growing interest in Intellectual Capital management and Knowledge Management is now reaching small companies, especially those in the Knowledge-Intensive Business Services (KIBS) sector. This paper aims to explore this issue, starting from the assumption that a planned and systematic approach to KM, as is used in large companies, is rarely applicable in small organizations. It is more likely that small companies adopt an approach to KM that could be defined as “emergent”, i.e. KM is not planned rationally and in advance, but emerges and is developed along with time. In the paper, the concept of emergent KM approach will be defined and discussed, and three research questions will be examined: a. Is it possible to detect an emergent KM approach in the practice of small KIBS? b. If so, why small KIBS companies follow an emergent KM approach? c. What particular features this approach can have in those companies? The study is based on the results of a qualitative survey involving several owners and managers of small companies operating in the KIBS sector. The survey uses the case study method, and gives grounds for a preliminary analysis of emergent KM approach is small companies offering KIBS. The findings confirm that it is easy to find small companies adopting an emergent approach to KM: in the analysed cases there were no formal KM plans, despite the fact that they have all introduced various KM practices. This shows that there can be the need to define KM approaches that better fit smaller companies
Keywords: L84; M1; 330; Knowledge Management; KIBS; Emergent KM Approach; Case-study analysis